Memaknai â€œKehendak-Mulah Yang Jadiâ€ Berdasarkan Lukas 22:42 dan Aplikasinya bagi Peningkatan Iman Anggota Gereja Toraja - Monika Jerry D. Londongna; Stephani Intan M. Siallagan; Deflit Dujerslaim Lilo (DIEGESIS: Jurnal Teologi Kharismatika, 2023)
The aim of this study is to find out the meaning of "Thy will be done" according to the Bible in Luke 22:42, to find the right application for the lives of Toraja Church members of the Gloria Buttutanga, Buakayu Klasis. The authors begin with an overview and background of Luke 22:42, as well as an analysis of the text and then describes the understanding of church members Gloria Church about "Thy will be done" and the practices of life that members of the Gloria Church should have based on the meaning of "Thy will be done" from Luke 22:42. The qualitative research methods used in this research are literature review and a field study. For literature studies, the researcher also used the hermeneutic method, while field studies are carried out by observation and interview.Â  First, the phrase "Thy will be done" in Luke 22:42 can be interpreted as a form of total surrender and perfect obedience from Jesus. Second, members of the Toraja Church congregation in Gloria Buttutanga who are still weak in faith due to the suffering of life experienced should surrender themselves to God in totality and continue to live in obedience despite the suffering of life.Keywords: God's will; obedience; faith; the suffering of life.AbstrakTujuan dari penelitian ini adalah untuk mengetahui makna â€œKehendak-Mulah Yang Jadiâ€ menurut Alkitab dalam Lukas 22:42 untuk menemukan penerapan yang tepat bagi kehidupan anggota Gereja Toraja Jemaat Gloria Buttutanga, Klasis Buakayu. Penulis memulai dengan gambaran umum dan latar belakang Lukas 22:42, serta analisis teks dan selanjutnya memaparkan pemahaman anggota jemaat Gloria Buttutanga Klasis Buakayu tentang â€œkehendak-Mulah yang jadiâ€ dan praktek kehidupan yang harus dimiliki oleh anggota Jemaat Gloria berdasarkan makna â€œkehendak-Mulah yang jadiâ€ dari Lukas 22:42. Metode penelitian kualitatif yang digunakan dalam peneltian ini adalah studi pustaka dan studi lapangan. Untuk studi pustaka, penulis gunakan juga metode hermeneutik sedangkan studi lapangan dilakukan dengan cara observasi dan wawancara. Temuan penelitian ini yaitu: pertama, frasa â€œKehendak-Mulah Yang Jadiâ€ di dalam Lukas 22:42 dapat dimaknai sebagai bentuk penyerahan diri total dan ketaatan yang sempurna dari Yesus. Kedua, anggota jemaat Gereja Toraja di Gloria Buttutanga yang masih lemah imannya karena penderitaan hidup yang dialami, seyogianya menyerahkan diri kepada Tuhan secara totalitas dan tetap hidup dalam ketaatan meski berada dalam penderitaan hidup.Kata kunci: kehendak Allah; ketaatan; iman; penderitaan hidup